Severe Acute Respiratory Syndrome Coronavirus-2 Infection in Children With Liver Transplant and Native Liver Disease: An International Observational Registry Study. Issue 6 (June 2021) - Kehar, Mohit; Ebel, Noelle H.; Ng, Vicky L.; Baquero, Jairo Eduardo Rivera; Leung, Daniel H.; Slowik, Voytek; Ovchinsky, Nadia; Shah, Amit A.; Arnon, Ronen; Miloh, Tamir; Gupta, Nitika; Mohammad, Saeed; et al.
ABSTRACT: Objective: Increased mortality risk because of severe acute respiratory syndrome coronavirus-2 (SARS-CoV2) infection in adults with native liver disease (LD) and liver transplant (LT) is associated with advanced age and comorbid conditions. We aim to report outcomes for children with LD and LT enrolled in the NASPGHAN/SPLIT SARS-CoV2 registry. Methods: In this multicenter observational cohort study, we collected data from 91 patients <21 years (LD 44, LT 47) with laboratory-confirmed SARS-CoV2 infection between April 21 and September 17, 2020. Results: Patients with LD were more likely to require admission (70% vs 43% LT, P = 0.007) and pediatric intensive care unit (PICU) management (32% vs 4% LT, P = 0.001). Seven LD patients required mechanical ventilation (MV) and 2 patients died; no patients in the LT cohort died or required MV. Four LD patients presented in pediatric acute liver failure (PALF), 2 with concurrent multisystem inflammatory syndrome in children (MIS-C); all recovered without LT. Two LD patients had MIS-C alone and 1 patient died. Bivariable logistic-regression analysis found that patients with nonalcoholic fatty LD (NAFLD) (odds ratio [OR] 5.6, P = 0.02) and LD (OR 6.1, P = 0.01, vs LT) had higher odds of severe disease (PICU, vasopressor support, MV, renal replacement therapy or death). Conclusions: Although not directly comparable, LT recipients had lower odds of severe SARS-CoV2 infection (vs LD), despite immunosuppression burden. NAFLD patients reported to the registry had higher odds of severe SARS-CoV2 disease. Future controlled studies are needed to evaluate effective treatments and further stratify LD and LT patients with SARS-CoV2 infection. Abstract : Supplemental Digital Content is available in the text